FEAR OF MISSING OUT AND MOTIVATION TO WORK TEACHER RAUDHATUL ATHFAL - Ismail, Ismail; Aziz, Azhar; Hasmayni, Babby (Psikis : Jurnal Psikologi Islami, 2023)
The absence of research studies with the theme of FOMO and motivation to work on early childhood teachers motivated researchers to conduct this study. This study aims to identify and analyze FOMO and motivation to work for PAUD teachers. This qualitative study uses a type of case study research to find out in more detail how FOMO in early childhood teachers and its impact on motivation to work in early childhood teachers. Respondents of this study were honorary PAUD teachers in Binjai city, as many as three people. Semi-structured interview techniques collected data, and data analysis was carried out by creating codes, categories, and data concepts. The results showed that the relationship between FOMO and motivation in learning is related to the intensity of social media access and well-being in social media that displays beautiful things. The implication of this study is to determine FOMO with motivation to work in early childhood teachers. This study explains the role of FoMO and social media engagement related to the psychological condition of early childhood teachers. This research is expected to open further discussions for research with related themes.